Out-of-hospital cardiac arrest patients treated with cardiopulmonary resuscitation using extracorporeal membrane oxygenation: focus on survival rate and neurologic outcome. Issue 1 (December 2016) - Lee, Jae; Han, Sang; Kim, Hyoung; Hong, Kyung; Choi, Hyun; Park, Kyu; Seo, Jeong; Lee, Tae; Kim, Heung; Kim, Seonju; Lee, Sun; Hwang, Sung; et al.
Abstract Background Extracorporeal membrane oxygenation (ECMO) is a useful treatment for refractory out-of-hospital cardiac arrest (OHCA). However, little is known about the predictors of survival and neurologic outcome after ECMO. We analyzed our institution's experience with ECMO for refractory OHCA and evaluated the predictors of survival and neurologic outcome after ECMO. Methods This was a retrospective review of the medical records of 23 patients who were treated with ECMO due to OHCA that was unresponsive to conventional cardiopulmonary resuscitation, between January 2009 and January 2014. Results Our ECMO team was activated within 10 min for refractory OHCA, and the 30-day survival rate was 43.5 %. In a multivariate analysis that evaluated independent factors contributing to mortality, urine output ≤ 0.5 mL · kg−1 · h−1 (defined as oliguria) during the 24 h after ECMO was statistically significant (OR, 32.271; 95 % CI, 1.379–755.282;p = 0.031). Just after ECMO implantation, 6 of the 9 patients (66.7 %) who had normal findings on brain computed tomography (CT) survived with a cerebral performance category (CPC) of grade 1. However, only 3 of the 11 patients (27 %) who had evidence of hypoxic brain damage on initial brain CT survived (their CPC grade was 4). Conclusions Based on our findings, the survival rate can be improved by rapid implantation of ECMO, and oliguria seen during the first 24 h after ECMO may be an independent predictor of mortality. Furthermore, findings on brain CT just after ECMO and subsequent images may represent an important predictor for neurologic outcome after ECMO.